Repeated sprints with directional changes: do angles matter? - Buchheit, M.; Haydar, B.; Ahmaidi, S. (Journal of Sports Sciences, 2012)
To examine whether performance, physiological and perceptual responses to repeated sprints including changes of direction are angle-dependent, twelve team-sport players performed (1) single 30-m sprints without or with two (45°, 90° or 135°) changes of direction and (2) repeated-sprint sequences matched for initial sprint time without (Line [6x30m]) or with (45° [6x28.0m], 90° [6x22.2m] or 135° [6x19.5m]) two changes of direction. For each sequence, mean sprint time (RSmean), peak heart rate (HRpeak), blood lactate concentration ([La]b) and rating of perceived exertion (RPE) were recorded. Results show that performance, physiological and perceptual responses were angle-dependent. Compared with Line, RSmean was likely lower for 45° (-1.7%(90%CL:-3.5;0.1); chances for greater/similar/lower values of 1/23/76%, respectively) and possibly greater for 135° (+0.8%(90%CL:-0.6;2.3), 44/53/3%). HRpeak, [La]b and RPE were likely greater for Line compared with the three other protocols. RPE during 45° was greater than during 90°(+14%(90%CL:8;19), 0/1/99%) and 135° (+11%(90%CL:1;22), 2/15/83%). The correlation coefficients describing the relationships between the four single 30-m sprints were <0.70; these for RSmean times were >0.70. Performance, physiological and perceptual response during repeated sprints with changes of direction are angle-dependent. However, unlike changes of direction speed, repeated-sprint ability with changes of direction is more likely to be a general quality.